2018
DOI: 10.1002/humu.23564
|View full text |Cite
|
Sign up to set email alerts
|

Germline variation in the oxidative DNA repair genesNUDT1andOGG1is not associated with hereditary colorectal cancer or polyposis

Abstract: The causal association of NUDT1 (=MTH1) and OGG1 with hereditary colorectal cancer (CRC) remains unclear. Here, we sought to provide additional evidence for or against the causal contribution of NUDT1 and OGG1 mutations to hereditary CRC and/or polyposis. Mutational screening was performed using pooled DNA amplification and targeted next-generation sequencing in 529 families (441 uncharacterized MMR-proficient familial nonpolyposis CRC and 88 polyposis cases). Cosegregation, in silico analyses, in vitro functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Polygenic inheritance has been shown to explain up to ∼15% of the familial CRC risk (Frampton et al, 2016) and at least two cases with CRC and possible digenic and oligogenic inheritance have been reported; these patients had variants in MUTYH and OGG1 (both involved in the base excision repair pathway) and in APC, OGG1, EXO1 and POLQ, respectively (Morak et al, 2011;Ciavarella et al, 2018). OGG1 was not part of our gene panel, and its role in hereditary CRC/polyposis is controversial (Smith et al, 2013;Mur et al, 2018). Intriguingly, we identified the same EXO1 variant in a patient with rectal cancer 31-yearsold (no.…”
Section: Discussionmentioning
confidence: 99%
“…Polygenic inheritance has been shown to explain up to ∼15% of the familial CRC risk (Frampton et al, 2016) and at least two cases with CRC and possible digenic and oligogenic inheritance have been reported; these patients had variants in MUTYH and OGG1 (both involved in the base excision repair pathway) and in APC, OGG1, EXO1 and POLQ, respectively (Morak et al, 2011;Ciavarella et al, 2018). OGG1 was not part of our gene panel, and its role in hereditary CRC/polyposis is controversial (Smith et al, 2013;Mur et al, 2018). Intriguingly, we identified the same EXO1 variant in a patient with rectal cancer 31-yearsold (no.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, MUTYH -null mice showed increased intestinal tumorigenesis and C:G>A:T transversion mutations (Sakamoto et al 2007). To date, germline variation in OGG1 and NUDT1 has not been associated with a Mendelian hereditary cancer predisposition, and MUTYH remains the only validated cancer predisposition gene linked to the SBS18/SBS36 signatures with a strong phenotype of C:G>A:T transversions (Mur et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For years, several groups undertook the study of OGG1 and NUDT1 (= MTH1 ) variants as potential causal factors of CRC predisposition. Several studies have been published, and what seemed to be promising mostly in the first years [ 22 , 23 , 24 , 25 , 26 ], reduced their degree of interest, at least as high- or moderate-risk genes, when subsequent larger studies suggested no causal association [ 27 , 28 , 29 ].…”
Section: Candidate Causal Genes For Mismatch Repair Proficient Hermentioning
confidence: 99%